Penyuluhan Hukum Problematika Tanah dan Penyelesaiannya di Negeri Wotay Maluku Tengah - Novyta Uktolseja; Jenny Kristiana Matuankotta; Pieter Radjawane; Harun Matayane (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: Land is a vital object that is very important for the community to carry out all activities and activities in support of community survival and development.Purposes of Devotion: Providing education and legal understanding for the community regarding land problems and their solutions so that land-related problems that often occur in the community can be resolved properly. Method of Devotion: Performed with the lecture method by each of the presenters. The lecturer is given time to deliver the material, after which the participants are invited to ask a problem or question, which is then answered in turn by the speaker according to the problem being asked.Results of the Devotion: Legal counseling in Negeri Wotay through panel discussions in which the presenters take turns delivering the material then continued with questions and answers between the presenters and the community, thus answering the lack of understanding of the community about the land law.